2020
DOI: 10.1111/jfpp.14767
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drying methods and temperatures on protein, pasting, and thermal properties of white floury corn

Abstract: Drying is a simultaneous process of heat and mass transfer between the product, which loses moisture, and the drying air, which provides energy (Dalpasquale, Sperandio, Monken e Silva, & Kolling, 2008). Field drying can cause grain quality loss, with insects and fungi infestation, and even increase the levels of mycotoxins in grains (Kaaya, Warren, Kyamanywa, & Kyamuhangire, 2005). High drying temperatures can reduce corn quality after storage. Some studies have showed that drying temperatures above 70 °C redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Drying is an important food preservation technique utilized to lower the moisture of a food product to a predetermined level (Berk, 2018; Timm et al., 2020). Prevention of microbial spoilage, reduction in enzymatic and metabolic activities and extension of storability are the prime objective of the drying process (Beigi et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Drying is an important food preservation technique utilized to lower the moisture of a food product to a predetermined level (Berk, 2018; Timm et al., 2020). Prevention of microbial spoilage, reduction in enzymatic and metabolic activities and extension of storability are the prime objective of the drying process (Beigi et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of drying temperature (70 and 90 °C) and stationary, intermittent (with 10 and 30 min of equalization), and heating with infrared radiation drying systems on the properties of protein and white farinaceous corn starch were studied by Timm et al (2020b) The results showed that the reduction in soluble protein and lipase activity was associated with the increase in drying temperature and the drying method used. Furthermore, the drying of white floury corn at 70 °C using the fixed bed method aims to maintain the protein solubility and paste properties of the flour (Timm et al, 2020b). Odjo et al (2012) studied the effect of drying temperature (60, 80, 100, and 120 °C) and hydrothermal treatment of corn kernels on the denaturation of salt-soluble proteins and reported that low grain moisture content resulted in a lower rate of protein denaturation.…”
Section: Effects On Technological Propertiesmentioning
confidence: 99%